Challenging Endovascular Treatment of Ruptured Proximal Posterior Inferior Cerebellar Artery Aneurysm: A Case Report - Prasetyo, Bambang Tri; Kurniawan, Ricky Gusanto; Rilianto, Beny; Windiani, Pratiwi Raissa; Kelvin, Kelvin Theandro (AKSONA, 2024)
Highlight: Posterior inferior cerebellar artery (PICA) aneurysms are rare in occurence. The endovascular management of PICA aneursysms is challenging due to anatomical difficulties in accessing the site. The rebleeding of PICA aneurysms, although rare than other intracranial anurysms, may still happen and must be considered in their management   ABSTRACT Introduction Aneurysms of the posterior inferior cerebellar artery (PICA) are rare clinical entities with a lower risk of rupture than other intracranial locations. This makes managing PICA aneurysms challenging and important for neurointerventionists to understand. In this case report, we looked at a rare case of PICA aneurysm with post-coiling rebleeding.  Case: We reported a 51-year-old female with complaints of dizziness and vomiting. The patient was found to be hypertensive and a neurologic assessment revealed neck stiffness and left hemiparesis. A computed tomography (CT) scan of the head indicated subarachnoid hemorrhage. CT angiography (CTA) showed an aneurysm at the right proximal PICA. Although endovascular coiling was performed, the patient rebleed one month later. Following the insertion of the second coil, successful embolization was achieved, and the patient showed clinical improvement. Conclusion: PICA aneurysms require careful endovascular management, considering the difficulty of access due to their anatomical location. An understanding of its proper management is of paramount importance to reducing mortality.